PERBEDAAN KEPUASAN KERJA PADA PEGAWAI OUTSOURCING DENGAN PEGAWAI TETAP PT. PLN (PERSERO) - Annisa N. Amrullah; Bambang S. Arifin; Nisa Hermawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
Industrial employee recently faced outsourcing system, a process transfering bisnis activity to the third parties. This system will give an impact to job satisfaction of the employee if they feel unfairly treated such as no fringe benefit and discriminated salary. This comparative research design compared between 45 permanent employee and 75 outsourcing employee at PT. PLN (PERSERO) UPJ Baleendah. Instrument used is job satisfaction scales from Herzberg. Statistical analysis used U Mann Whitney to test hypothesis proposed. Result using 95% trusted degree (α = 0,05) found p > α. It is concluded that Ho is accepted and H1 is not. Therefore, there is no significant differences between outsourcing employee and permanent employee at di PT. PLN (PERSERO).